The Implementation of Artificial Intelligence in Electronic Commerce - Tessa Handra; Nuke Puji Lestari Santoso; Oliver Wilson; Tarisya Ramadhan (Universitas Raharja, 2024)
This research aims to explore the implementation of Artificial Intelligence (AI) within the context of electronic commerce. As digital technology evolves, AI has become a crucial tool in transforming the way businesses operate online. This study employs both qualitative and quantitative approaches to analyze how AI can enhance the online shopping experience, including personalization, customer service automation, and data analysis for market trend prediction. Through case studies on several leading e-commerce platforms, this research identifies key AI applications such as recommendation systems, chatbots, and price optimization algorithms. The findings indicate that the implementation of AI not only improves operational efficiency but also provides a more personalized and responsive experience for consumers. The study also addresses the challenges and ethical implications of using AI in e-commerce, including issues of data privacy and algorithmic bias. By providing comprehensive insights into the current applications of AI and its potential for the future, this research aims to guide developers, entrepreneurs, and researchers in integrating effective and ethical AI solutions into e-commerce business strategies.